Effects of Individual and combined fermentation factors on antimicrobial activity of Nisin by Lactococcus lactis ATCC 11454 - Mohd Rasid, Nur Hidayah; Abdul Halid, Nadrah; Song, Adelene Ai Lian; Sabri, Suriana; Saari, Nazamid; Hasan, Hanan (Springer, 2022)
There is an increasing demand for natural food preservatives due to consumers’ concern on the negative effects of chemical preservatives in food products. Nisin (bacteriocin) is an effective food biopreservative that has been approved globally. However, its low yield proves to be a limiting factor and must be addressed to meet the increasingly high demand from the food industry. The present work thus investigated the effects of individual and combined fermentation factors on Lactococcus lactis ATCC 11454 growth and nisin activity using the one-factor-at-a-time (OFAT) method. The level of each factor that gave the highest nisin production was then selected and combined to further improve its activity. The best combined conditions for highest cell growth and nisin activity were 30 °C, pH 6.0, and mild agitation with the addition of 1.0% w/v glucose, 1.0% w/v skim milk, and 0.5% v/v Tween 20. This increased nisin production by 22.7% as compared to control (basic condition). The present work provided critical information on the relationship between fermentation conditions, growth, and nisin activity of L. lactis ATCC 11454 that could be explored to understand the potential and limitation of the strain. This fermentation strategy can also serve as a benchmark to further enhance the production of bacteriocin or other biopreservative compounds.